Win a prize draw! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
This is not a competition between readers, because everyone uses Spore in a unique way, and each one is important. But to encourage you to write in, we shall hold a random prize draw. On 1 March 2002, at CTA headquarters, we shall put all entries...